Rancang Bangun Aplikasi Pengelolaan Pada Apotek Sinar Jaya - Panjaya, Michael Richie; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Existing activities in the Pharmacies Sinar Jaya namely the process of selling the pharmacies Sinar Jaya that customers make orders to the sales department, sales department provides customer request to the warehouse to check demand the drug, when the drug is requested is available, then the warehouse will give part sales, parts sales will make a memorandum in duplicate, one sheet will be provided to customers as well as the requested drug. One sheet was again kept on file. some constraints on the sale of drugs at pharmacies, namely in the warehouse not have a standard in recording drug stocks, do not have a minimum stock in the drug warehouse stock control for the warehouse just ordered the item if the amount of the stock is getting low. Reports on sales was recorded using excel. Based on the analysis of sales reports in november and december 2014, has a percentage of 32% of goods are often sold but the inventory is empty, unsold goods are 10% and 59% the rest of the items contained in the drug stocks.                         From the test results of applications that have been done on Pharmacy Sinar Jaya, the conclusions that can be drawn is the app has generated information about System Administration on Sales to menentukana minimum stock on each - each drug and report details of a report on drug sales, information items behavior in the selling, and monitoring of expired goods.Keywords: Management,Aplication, Drug Stock, .